The Formulation of Islamic Bank Performance Based on Contemporary Maqasid al-Sharia - Luhur Prasetiyo; Khusniati Rofiah (Justicia Islamica, 2021)
The current measurement of the performance of Islamic banks is more on financial performance. Islamic banks have two significant roles different from conventional banks: business and social. Financial performance evaluates the business role of Islamic banks. Meanwhile, the social role of Islamic banks has not yet received an equal portion of the measurement. This article proposes an Islamic bank performance measurement system based on Sharia economic goals. This formulation is necessary to adjust the performance assessment of Islamic banks based on Islamic economic goals. By using content analysis, this research used the contemporary Maqasid al-sharia approach. To formulate a measurement of the Islamic bank performance based on the roles and objectives of Islamic economics, contemporary maqasid al-sharia was employed as the construction basis. Based on the contemporary maqasid al-sharia, the Islamic bank's performance formulation can be broken down. Then, factors in assessing Islamic bank performance can be determined on financial and social aspects. Thus, Islamic banks are in line with the goals of Islamic economics, fighting for justice and the welfare of the community (falah), the objectives of sharia (maqasid al-sharia), and the primary goal of Islamic law (masalih al-'ibad).